Atezolizumab with or without bevacizumab and platinum-pemetrexed in patients with stage IIIB/IV non-squamous non-small cell lung cancer with EGFR mutation, ALK rearrangement or ROS1 fusion progressing after targeted therapies: A multicentre phase II open-label non-randomised study GFPC 06-2018. (April 2023) - Bylicki, Olivier; Tomasini, Pascale; Radj, Gervais; Guisier, Florian; Monnet, Isabelle; Ricordel, Charles; Bigay-Game, Laurence; Geier, Margaux; Chouaid, Christos; Daniel, Catherine; Swalduz, Aurelie; Toffart, Anne-Claire; et al.
Abstract: Background: Previous reports showed limited efficacy of immune checkpoint inhibitors as single-agent treatment for non-small cell lung cancer (NSCLC) with epidermal growth factor receptor ( EGFR ) mutation or ALK/ROS1 fusion. We aimed at evaluating the efficacy and safety of immune checkpoint inhibitor combined with chemotherapy and bevacizumab (when eligible) in this patient subgroup. Methods: We conducted a French national open-label multicentre non-randomised non-comparative phase II study in patients with stage IIIB/IV NSCLC, oncogenic addiction ( EGFR mutation or ALK/ROS1 fusion), with disease progression after tyrosine kinase inhibitor and no prior chemotherapy. Patients received platinum, pemetrexed, atezolizumab, bevacizumab (PPAB cohort) or, if not eligible to bevacizumab, platinum–pemetrexed–atezolizumab (PPA cohort). The primary end-point was the objective response rate (RECIST v1.1) after 12 weeks, evaluated by blind independent central review. Results: 71 patients were included in PPAB cohort and 78 in PPA cohort (mean age, 60.4/66.1 years; women 69.0%/51.3%; EGFR mutation, 87.3%/89.7%; ALK rearrangement, 12.7%/5.1%; ROS1 fusion, 0%/6.4%, respectively). After 12 weeks, objective response rate was 58.2% (90% confidence interval [CI], 47.4–68.4) in PPAB cohort and 46.5% (90% CI, 36.3–56.9) in PPA cohort. Median progression-free survival and overall survival were 7.3 (95% CI 6.9–9.0) months and 17.2 (95% CI 13.7–NA) months in PPAB cohort and 7.2 (95% CI 5.7–9.2) months and 16.8 (95% CI 13.5–NA) months in PPA cohort, respectively. Grade 3–4 adverse events occurred in 69.1% of patients in PPAB cohort and 51.4% in PPA cohort; Grade 3–4 atezolizumab-related adverse events occurred in 27.9% and 15.3%, respectively. Conclusion: Combination approach with atezolizumab with or without bevacizumab and platinum-pemetrexed achieved promising activity in metastatic EGFR -mutated or ALK/ROS1 -rearranged NSCLC after tyrosine kinase inhibitor failure, with acceptable safety profile. Highlights: Single-agent immune checkpoint inhibitor has not shown efficacy for non-small cell lung cancer with epidermal growth factor receptor mutation or ALK fusion. Chemo-immunotherapy ± bevacizumab shows an acceptable objective response rate for a 2/3-line treatment. The progression-free survival in both cohorts is interesting in this subgroup of patients. Tolerance is acceptable in both treatment arms.